Hollow and highly diastereoselective face-rotating polyhedra constructed through rationally engineered facial units. Issue 35 (6th August 2021) - Tang, Xiao; Li, Zhihao; Liu, Haoliang; Qu, Hang; Gao, Wenbin; Dong, Xue; Zhang, Shilin; Wang, Xinchang; Sue, Andrew C.-H.; Yang, Liulin; Tan, Kai; Tian, Zhongqun; et al.
Abstract : The rationally engineered facial units, TAT- m and TAT- p, resulted in distinct diastereoselectivity of face-rotating polyhedra (FRP). Abstract : Molecular face-rotating polyhedra (FRP) exhibit complex stereochemistry, rendering it challenging to manipulate their assembly in a stereoselective manner. In our previous work, stereocontrolled FRP were gained at the cost of losing the confined inner space, which hampers their host–guest interactions and potential applications. Through a rational design approach, herein we demonstrate the successful construction of hollow FRP with high diastereoselectivity. Whereas the [4 + 4] imine condensation of meta -formyl substituted C 3h -symmetric TAT- m and C 3 -symmetric Tri-NH2 led to the formation of all feasible FRP-12 diastereoisomers; the para -substituted constitutional isomer, TAT- p, exclusively assembled into a pair of homo-directional enantiomeric FRP-13 - CCCC / AAAA with a cavity size larger than 600 Å 3 . Detailed structural characterizations and theoretical investigations revealed the thermodynamic landscape of FRP assembly can be effectively shaped by modulating the van der Waals repulsive forces among the facial building blocks. Our work provided a novel strategy towards stereospecific assembly of pure organic cages, opening up new opportunities for further applications of these chiral materials.